Sam37 is crucial for formation of the mitochondrial TOM–SAM supercomplex, thereby promoting β-barrel biogenesis - Wenz, Lena-Sophie (J Cell Biol, 2015)
Biogenesis of mitochondrial β-barrel proteins requires two preprotein translocases, the general translocase of the outer membrane (TOM) and the sorting and assembly machinery (SAM). TOM and SAM form a supercomplex that promotes transfer of β-barrel precursors. The SAM core complex contains the channel protein Sam50, which cooperates with Sam35 in precursor recognition, and the peripheral membrane protein Sam37. The molecular function of Sam37 has been unknown. We report that Sam37 is crucial for formation of the TOM–SAM supercomplex. Sam37 interacts with the receptor domain of Tom22 on the cytosolic side of the mitochondrial outer membrane and links TOM and SAM complexes. Sam37 thus promotes efficient transfer of β-barrel precursors to the SAM complex. We conclude that Sam37 functions as a coupling factor of the translocase supercomplex of the mitochondrial outer membrane.